SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT DIABETES MENGGUNAKAN METODE CERTAINTY FACTOR - Sujiati, Endang; Sulindawaty, Sulindawaty (Jurnal Sistem Informasi Kaputama (JSIK), 2020)
Diabetes is a health disorder where a person’s blood suger levels are higher due to lack of insulin or insulin receptors do not funtion properly. Initially many people did not know that they were suffering from diabetes, people with diabetes only found themselves suffering from diabetes after experiencing complications in various organs of the body. This ignorance is caused by the lack of information about diabetes and its symptoms. This study aims to create an expert system that uses the Certainty Factor method as a tool in dignosing diabetes. Consultation on this system is in the from of interactive dialogue between user and expert system on diabetes. The user selects the symptoms proposed by the system, and the system provides the results of the drop disease that the user has suffered.